Premarital Training as a Preventive Strategy for Divorce in Kapanewon Ngemplak - Anisah Budiwati; Yusdani Yusdani; Raden Agung Nugraha (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2026)
Marriage guidance is a program initiated by the Ministry of Religious Affairs to equip engaged couples with the knowledge and skills needed to build and maintain a harmonious and sustainable family life. However, despite the many programs designed to prepare couples for marriage, divorce rates have continued to increase over the past ten years. Collaboration between academic institutions and the government, represented in this context by the Office of Religious Affairs (KUA/Kantor Urusan Agama), plays a vital role in nation-building efforts through the implementation of premarital preparation programs. The KUA has consistently facilitated this program as a preventive measure to address the increasing divorce rate. The premarital course is designed to (1) encourage community involvement in supporting the formation of sakinah (harmonious) families, (2) raise awareness of the importance of adequate preparation before marriage, and (3) integrate psychological and Islamic economic perspectives into marriage readiness initiatives. The program used several methods, including (1) structured discussions during training sessions, (2) interviews, and (3) analysis and evaluation of field data and training outcomes. The findings indicate that the government’s role in Kapanewon Ngemplak has been effectively carried out in collaboration with local university academics. This initiative received positive responses for contributing to better-prepared marriages. Nevertheless, maintaining family harmony remains a challenge, because efforts to build family resilience must continue beyond the wedding ceremony. Premarital training was conducted not only to prevent divorce but, more importantly, to address and prevent conflicts before they lead to divorce.